Use of efficient microorganisms in a sustainable production of pigs intended for fattening - Vera–Rodríguez, José Humberto; Álvarez Sánchez, Ana Ruth (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
The aim of this study was to evaluate the productive response and welfare of pigs destined for fattening when inoculating efficient microorganisms to the drinking water. In total, 180 F2 pigs of the Topigs Norsvin genetic line were used from 22 to 164 days of age, distributed in completely randomized DBCA blocks with 12 treatments and 3 repetitions (n = 5 pigs per experimental unit). The treatments were: T0 (Control), T1 (Lactobacillus acidophilus), T2 (Enterococcus faecium), T3 (Bifidobacterium bifidum), T4 (Bacillus subtilis), T5 (L. acidophilus and E. faecium), T6 (L. acidophilus and B. bifidum), T7 (L. acidophilus and B. subtilis), T8 (E. faecium and B. bifidum), T9 (E. faecium and B. subtilis), T10 (B. bifidum and B. subtilis), T11 (L. acidophilus, E. faecium, B. bifidum and B. subtilis) supplied in the pre–fattening and fattening stage, at a dose of 700 g·200 L-1 (1 × 109 CFU·g-1), distributed in 5 frequencies every 30 d (22, 52, 82, 112 and 142 days of age). The T7 treatment was one of the treatments with the best results for all the variables (final weight, accumulated feed intake, daily weight gain, feed conversion, hot carcass yield and presentation of diarrhoea). It is concluded that the use of these microorganisms in the drinking water of pigs destined for fattening has a favourable effect on the efficiency of absorption and conversion of nutrients at the intestinal level, reflecting an improvement in production rates and a reduction in the incidence of diarrhoea when using the microbial consortium (L. acidophilus and B. subtilis).